Intimate Partner Violence Against Women During the COVID-19 Lockdown in Italy: A Multicenter Survey Involving Anti-Violence Centers. (July 2022) - Romito, Patrizia; Pellegrini, Martina; Saurel-Cubizolles, Marie-Josèphe
This study explores intimate partner violence (IPV) evolution during the lockdown with a sample of 238 women (44% cohabitating and 56% not cohabitating with the perpetrator), attending five antiviolence centers in Italy (June–September 2020). Questions included 12 items on IPV and, for each item, a question about whether violence increased/stayed the same/decreased during lockdown; an indicator of IPV modifications was constructed. Two distinct patterns, confirmed after adjustment for socio-demographic factors, emerged: IPV increased for 28% of cohabitating and decreased for 56% of non-cohabitating women. Such results suggest the efficacy of physical distancing—strictly controlled by the State—in the prevention of IPV.